1997
DOI: 10.1103/physrevlett.79.5146
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Spin Dynamics of Ferromagnetic Thin Films Observed by fs Spin-Resolved Two-Photon Photoemission

Abstract: Using a "pump and probe" technique, the time scale of spin relaxation effects in ferromagnetic thin films is investigated. Samples are excited by a 3 eV "pump" laser pulse ͑t ഠ 170 fs͒, and electrons are photoemitted by a 6 eV "probe" pulse, after delays ranging up to 1 ns. The spin polarization of the photoelectrons is measured using a Mott detector. The time dependence of the spin polarization of thin Ni films on Ag is explained in a local magnetic moment picture with two excitation processes. Stoner excitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
172
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(183 citation statements)
references
References 15 publications
8
172
2
Order By: Relevance
“…[1]. The SLR time in Ni is about 304 ps as calculated from a formalism similar to that applied to Gd before [6], which can be compared with the experimental value of 400 ps in Ni [16]. From our calculation it is suggested that the high-speed limit of spin dynamics is about tens of femtoseconds, which is not yet exhausted by experiments.…”
mentioning
confidence: 68%
“…[1]. The SLR time in Ni is about 304 ps as calculated from a formalism similar to that applied to Gd before [6], which can be compared with the experimental value of 400 ps in Ni [16]. From our calculation it is suggested that the high-speed limit of spin dynamics is about tens of femtoseconds, which is not yet exhausted by experiments.…”
mentioning
confidence: 68%
“…Since the observation by Beaurepaire et al that excitation by femtosecond laser pulses can induce a demagnetization in a nickel thin film on a subpicosecond time scale, 1 laserinduced magnetization dynamics received a growing attention. [2][3][4][5][6][7][8] The possibility of optically manipulating spins on such an ultrafast time scale offers, indeed, many potential applications in technology. Beside the technological relevance, research in this field is motivated by scientific interest, the microscopic mechanisms that lead to ultrafast magnetization response being not yet fully understood.…”
Section: Influence Of Photon Angular Momentum On Ultrafast Demagnetizmentioning
confidence: 99%
“…However, as it has been discussed in recent papers on Ni [6][7][8][9], it is premature to directly connect the MOKE signal with demagnetization in such ultrafast time scale.…”
mentioning
confidence: 99%
“…Typeset using REVT E X 1 Control and manipulation of spins by ultrafast optical excitation, which gives rise to photo-induced magnetization change and magnetic phase transitions in dilute magnetic semiconductor quantum structures [1][2][3], doped semiconductors [4] and ferromagnetic metals [6][7][8][9][10], have attracted considerable attention. Recent study on the magnetization dynamics in the photo-excited Ni films with nonlinear optical techniques has revealed ultrafast spin process within 50 fs [9].…”
mentioning
confidence: 99%